2022
DOI: 10.18863/pgy.952664
|View full text |Cite
|
Sign up to set email alerts
|

Huntington Hastalığı’nın Nöropsikiyatrik Yönü

Abstract: Huntington's Disease is a progressive neurodegenerative disorder inherited in an autosomal dominant fashion with distinct phenotypes as chorea and dystonia, incoordination, cognitive disorders, and behavioural problems. In addition to cognitive and motor symptoms, neuropsychiatric symptoms are among the core symptoms of the disease. Neuropsychiatric symptoms are quite common in Huntington's Disease and the prevalence of neuropsychiatric disorders in different stages of the disease is estimated to be 33-76%. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…As it progresses, there is a need for a long or even 24 hour care [55]. Also, many people with HD commit suicide, with a risk estimated to be from 2 to 7 times greater than in general population [5,12,19,21,22,25,77]. It is suggested that the risk of suicide in HD is related to the fact that the disease is neurodegenerative, progressive, seriously hampering functioning in many areas of the patient's life, with the awareness of the lack of effective treatment, and on the other hand, suicidal behavior is not related to perseverative behavior [19,24,64].…”
Section: E a R L Y B I R Dmentioning
confidence: 99%
See 4 more Smart Citations
“…As it progresses, there is a need for a long or even 24 hour care [55]. Also, many people with HD commit suicide, with a risk estimated to be from 2 to 7 times greater than in general population [5,12,19,21,22,25,77]. It is suggested that the risk of suicide in HD is related to the fact that the disease is neurodegenerative, progressive, seriously hampering functioning in many areas of the patient's life, with the awareness of the lack of effective treatment, and on the other hand, suicidal behavior is not related to perseverative behavior [19,24,64].…”
Section: E a R L Y B I R Dmentioning
confidence: 99%
“…Usually, imaging techniques are applied to find biomarkers for HD, in particular for its pre-manifest stage (preHD). Despite rapid medicine development, neither cure nor therapy for this disease are available [5,20]; therefore, finding appropriate biomarkers plays crucial role at the preHD stage in order to make the potential symptomatic treatment more efficient and to improve life quality of affected persons [20].…”
Section: State Of the Art -Neuroimaging Techniquesmentioning
confidence: 99%
See 3 more Smart Citations